Management of denture stomatitis in removable dentures wearers - Indriani Oktaria (Indonesia Prosthodontic Association, 2023)
Denture stomatitis (DS) is a pathological change in the oral mucosa that commonly occurs in denture users, which is characterized by an inflammatory reaction and erythema in the oral mucosa that is in contact with the denture. Cli-nical manifestations often include red lesions due to excessive occlusal trauma, frequently occurring in the palatal mucosa region. Loose and unstable prosthesis use can also be a predisposing factor for DS. This paper discusses cases of DS in patients with complete dentures (CD) and partial complex dentures. Chronic irritation due to heavy traumatic occlusion results in reduced stability of dentures. The fabrication of CD with proper vertical dimension set-ting and selection of smaller teeth elements can reduce progressive alveolar bone resorption. The use of topical gel medication like Oxyfresh can be an alternative in the clinical management of DS cases. Control of systemic conditi-ons, especially in the presence of comorbidities, is crucial to minimize the risk of DS occurrence and expedite the healing process if it does occur. Maintaining oral hygiene and denture cleanliness are also key factors for the suc-cess of optimal denture care.